2019
DOI: 10.1021/acs.jpca.9b03228
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of Zn(II)–Triazoles with CO2 and H2O: Structures, Energetics, and Applications

Abstract: Using a first-principle methodology, we investigate the stable structures of the nonreactive and reactive clusters formed between Zn2+–triazoles ([Zn2+-Tz]) clusters and CO2 and/or H2O. In sum, we characterized two modes of bonding of [Zn2+-Tz] with CO2/H2O: the interaction is established through (i) a covalent bond between Zn2+ of [Zn2+-Tz] and oxygen atoms of CO2 or H2O and (ii) hydrogen bonds through N–H or C–H of [Zn2+-Tz] and oxygen atoms of H2O or CO2, N–H···O. We also identified intramolecular proton tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…This was already established for Zn 0/+/2+ -imidazole and Zn 2+ -triazole complexes either isolated or interacting with CO 2 or H 2 O. [68][69][70][71] We should note that for both types of interactions which participate in the formation of these complexes, we demonstrate that all used ab initio and DFT methods predict a greater stability for the halogen interaction. Indeed, Table 3 shows that the I-bonded complexes are more stable than the respective O-bonded ones.…”
Section: Interaction Energiessupporting
confidence: 78%
See 1 more Smart Citation
“…This was already established for Zn 0/+/2+ -imidazole and Zn 2+ -triazole complexes either isolated or interacting with CO 2 or H 2 O. [68][69][70][71] We should note that for both types of interactions which participate in the formation of these complexes, we demonstrate that all used ab initio and DFT methods predict a greater stability for the halogen interaction. Indeed, Table 3 shows that the I-bonded complexes are more stable than the respective O-bonded ones.…”
Section: Interaction Energiessupporting
confidence: 78%
“…This was already established for Zn 0/+/2+ –imidazole and Zn 2+ –triazole complexes either isolated or interacting with CO 2 or H 2 O. 68–71…”
Section: Resultsmentioning
confidence: 55%
“…The presence of H 2 O could lead to the formation of hydronium carbamate according to eq . ,, Hydronium has also been proposed to play an important role in a number of systems involving CO 2 and H 2 O. ,, The simulated infrared spectrum of hydronium carbamate, TEPA 2 -N (1) H­(H 3 O + NCOO – ), in Figure b shows that both asymmetric ν a (OCO – ) vibration and symmetric ν s (OCO – ) vibration, characteristic bands for the carbamate structure, in the simulated spectrum of hydronium carbamate fall in the same range of ammonium carbamate in Figure a. The formation of hydrogen bonding between hydronium ion and carbamate ion led to the ν­(O–H + ··· – OCO) vibration at 2827 cm –1 for TEPA 2 -N (1) H­(H 3 O + NCOO – ) in Figure b and at 2470 cm –1 for TEPA 2 -N (3) (H 3 O + NCOO – ) + (H 2 O) 3 in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, solvent effects were examined using self‐consistent reaction field theory or by considering explicitly a water molecule closely interacting with the reactants and TSs. Indeed, previous theoretical and experimental works showed that the closest solvent molecule to the reactants plays the most important role in solvents 53–57 . The case of NaBr as a green catalyst is also examined.…”
Section: Introductionmentioning
confidence: 99%